2015
DOI: 10.1016/j.addr.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Development of mesoporous silica-based nanoparticles with controlled release capability for cancer therapy

Abstract: Nanoparticles that respond to internal and external stimuli to carry out controlled release of anticancer drugs have been developed. In this review, we focus on the development of mesoporous silica based nanoparticles, as this type of materials provides a relatively stable material that is amenable to various chemical modifications. We first provide an overview of various designs employed to construct MSN-based controlled release systems. These systems respond to internal stimuli such as pH, redox state and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
147
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(149 citation statements)
references
References 99 publications
0
147
0
2
Order By: Relevance
“…The straightforward synthesizing process enables the scaled-up manufacture of MSN for inhalation exposure test assays11. Thus, aPM 2.5 particles were prepared with MSN as the core and three chemical species loaded into the pores of MSN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The straightforward synthesizing process enables the scaled-up manufacture of MSN for inhalation exposure test assays11. Thus, aPM 2.5 particles were prepared with MSN as the core and three chemical species loaded into the pores of MSN.…”
Section: Resultsmentioning
confidence: 99%
“…Mesoporous silica nanoparticles (MSN) are advantageous for harboring the major chemical components of PM 2.5 because of their special structure with numerous small pores; these chemicals can adhere to the large inner surface of the pores11. Previous studies have reported that the primary injury associated with airborne particulate matter exposure is mainly localized in the respiratory system, causing inflammation and a reduction in lung function129, and the health effects is largely associated with the oxidative potential (OP) of PM 2.5 particles12.…”
mentioning
confidence: 99%
“…Another strategy is by the exposure of magnetic particles to oscillating magnetic field resulting in heat generation due to superparamagnetic property, where this temperature increase can be used to allow opening of a nanovalve, further triggering the drug release. [61] DNA-assembled gold-nanorod superstructures are also applied to tune the drug loading and releasing process due to its unique NIR induced photothermal effect. [62] These stimuli-responsive nanomedicines can precisely control the spatio-temporal drug release that offers the possibility to protect the drugs from degradation, allows direct localization or release of the payloads, and facilitates the maximum release at the target tissue/cell.…”
Section: Second Generation Nanomedicinesmentioning
confidence: 99%
“…[52] Additionally, controlled release is being investigated in MSNs because they can be chemically modified due to their stability and because MSN synthesis is relatively facile. [53] The synthesis of MSNs begins with one of two precursors: either tetraalkooxysilanes or sodium silicate solutions. Different templating agents such as ionic surfactants, pluronic surfactants, and neutral block copolymers are further used to influence pore size and arrangement as well the MSN's general shape and size.…”
Section: Mesoporous Silica-based Nanoparticlesmentioning
confidence: 99%